2019
DOI: 10.1111/puar.13104
|View full text |Cite
|
Sign up to set email alerts
|

Does Strategic Planning Improve Organizational Performance? A Meta‐Analysis

Abstract: Strategic planning is a widely adopted management approach in contemporary organizations. Underlying its popularity is the assumption that it is a successful practice in public and private organizations that has positive consequences for organizational performance. Nonetheless, strategic planning has been criticized for being overly rational and for inhibiting strategic thinking. This article undertakes a meta-analysis of 87 correlations from 31 empirical studies and asks, Does strategic planning improve organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
210
1
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(238 citation statements)
references
References 60 publications
6
210
1
21
Order By: Relevance
“…This analysis suggested that, on average, strategic planning (when formal and comprehensive) has a positive impact on organizational performance; and this impact becomes particularly potent when organizational performance is measured as an organization's ability to achieve its goals (i.e. effectiveness) (George et al, 2019). It is noteworthy that George et al's meta-analysis identified the importance of strategic planning being formal as well as comprehensive.…”
Section: Evidence From Empirical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis suggested that, on average, strategic planning (when formal and comprehensive) has a positive impact on organizational performance; and this impact becomes particularly potent when organizational performance is measured as an organization's ability to achieve its goals (i.e. effectiveness) (George et al, 2019). It is noteworthy that George et al's meta-analysis identified the importance of strategic planning being formal as well as comprehensive.…”
Section: Evidence From Empirical Researchmentioning
confidence: 99%
“…A number of published research studies has shown, first, that individual public sector managers often feel strategic planning has a range of benefits for them (see Flynn & Talbot, 1996); and, second, that strategic planning makes a positive contribution to public service performance at the organizational level (for example Johnsen, 2016;Poister, Pasha, & Edwards, 2013). A recent meta-analysis (incorporating evidence from almost 9,000 public and private sector organizations) has now shown that strategic planning 'works' (George, Walker, & Monster, 2019). This analysis suggested that, on average, strategic planning (when formal and comprehensive) has a positive impact on organizational performance; and this impact becomes particularly potent when organizational performance is measured as an organization's ability to achieve its goals (i.e.…”
Section: Evidence From Empirical Researchmentioning
confidence: 99%
“…Organizations sometimes fear a loss of power, autonomy, or control over budget (Perri 6 et al , 66; Peters ; Pollitt ; Tosun and Lang ). Moreover, the government apparatus in most countries has strong sectoral “silos” and many (semi)autonomous agencies, with an emphasis on accountability for organization‐specific objectives and targets (Bouckaert, Peters, and Verhoest ; Christensen and Lægreid ; George, Walker, and Monster ). As the results of HPPs often are not immediately visible in organization‐specific indicators, “minding the own shop” is the first priority (Perri 6 et al , 66).…”
mentioning
confidence: 99%
“…Two central principles based on findings from recent meta‐analyses published in Public Administration Review lie at the heart of the developed guide: (1) for performance management to enhance public service performance, it is important that performance data can be (and is) benchmarked between different entities (Gerrish 2016); and (2) decisions grounded in an understanding of capacity and environment, strengths and weaknesses, and systemic, data‐based analyses are more likely to enhance public service performance (George, Walker, and Monster 2019). These principles run through the entire development process of the guide to benchmarking COVID‐19 performance data.…”
Section: Developing a Guidementioning
confidence: 99%